Multiple functions of Ldb1 required for β-globin activation during erythroid differentiation - Song, Sang-Hyun (American Society of Hematology, 2010)
Ldb1 and erythroid partners SCL, GATA-1, and LMO2 form a complex that is required to establish spatial proximity between the β-globin locus control region and gene and for transcription activation during erythroid differentiation. Here we show that Ldb1 controls gene expression at multiple levels. Ldb1 stabilizes its erythroid complex partners on β-globin chromatin, even though it is not one of the DNA-binding components. In addition, Ldb1 is necessary for enrichment of key transcriptional components in the locus, including P-TEFb, which phosphorylates Ser2 of the RNA polymerase C-terminal domain for efficient elongation. Furthermore, reduction of Ldb1 results in the inability of the locus to migrate away from the nuclear periphery, which is necessary to achieve robust transcription of β-globin in nuclear transcription factories. Ldb1 contributes these critical functions at both embryonic and adult stages of globin gene expression. These results implicate Ldb1 as a factor that facilitates nuclear relocation for transcription activation.